Patients’ Experiences of Outcome Expectations in Renal Denervation: A Qualitative Study - Dandan Huang; Dayu Tang; Xi Chen; Shuting Zhu; Meiqi Yao; Jianping Song (Healthcare, 2026)
Objectives: To investigate the outcome expectations of patients undergoing renal denervation (RDN), clarify the contextual factors contributing to their development, characterize their content and attributes, and provide evidence for the development of structured perioperative intervention strategies. Methods: Purposive sampling was used to recruit 17 patients undergoing RDN as interview participants. Guided by Social Cognitive Theory (SCT), a qualitative descriptive design was adopted, and semi-structured interviews were conducted. Data were analyzed using inductive thematic analysis. Results: Three major themes and 10 subthemes were identified: formation of outcome expectations (expectations triggered by prior treatment frustration, expectations strengthened by risk perception, treatment expectations driven by medication burden, and expectations shaped by social information); regulation of outcome expectations (cognitive trade-offs triggered by uncertainty regarding RDN efficacy, and establishment of defensive psychological expectations); and readjustment of outcome expectations (validation of expectations based on outcome feedback, emotional experiences triggered by expectation discrepancy, psychological adjustment driven by unfavorable outcomes, and behavioral adjustment guided by support needs). Conclusions: Outcome expectations among patients undergoing RDN for hypertension management are dynamic and complex. These findings suggest that multidimensional assessment, individualized information guidance, attention to cognitive and emotional expectations, and continuing follow-up support may be useful directions for future nursing research and practice. Such measures may support the development of realistic outcome expectations, reduce postoperative psychological discrepancies, and improve treatment adherence and satisfaction.